Complex training methods for sprinters, jumpers and throwers (IAAF @-Letter for CECS Level II Coaches, 2003)
The term complex training was introduced in 1966 by Y. Verkhoshansky as describing a "complex of exercises united according to the principle that basic exercise for the development of reactive ability is fulfilled in a background of heightened excitability of the central nervous system, brought about by preliminary fulfillment of exercise requiring great power." (See Ebben/Jensen/Blackard 2000, 451) Verkhoshansky used the example of the perception of lifting a half-full can of water when you think it`s full. The excitability of the central nervous system responds in such a way that the water literally flies in the air because of the force applied. This shows that if the body thinks it has to do more heavy work, it will remember what is necessary to lift the full can and will react accordingly. By doing a light-weight exercise after a heavy-weight exercise one fools, as it were, the body into remembering the heavy weight. One, therefore, obtains high velocity of movement which will develop power. In light of established principles of strength and conditioning, the following recommendations on designing a complex training program can be offered.